Bioreduction properties of Pometia pinnata J. R. Forst. & G. Forst (Sapindaceae) for silver nanoparticles synthesis. Issue 1 (March 2020) - Pridyantari, A P; Ningrum, A S; Handayani, W; Imawan, C
Abstract: Plant extracts have been recognized as a substitute for chemical reducing agents in the synthesis of nanoparticles. Plants with antioxidants, including phenols and flavonoids, are expected to be reducing agents. Preliminary research has shown that Pometia pinnata (Matoa) stem bark aqueous extract can be used for silver nanoparticle (AgNP) biosynthesis. However, the compounds that serve as reducing agents in this process are still unknown. In this study, we studied antioxidant strength using DPPH radical reduction method. AgNP biosynthesis was performed by mixing powdered Matoa stem bark aqueous extract (2 %) with 1 mM AgNO3 (1:2). Further, pH of the Matoa stem bark aqueous extract was varied (pH 4, 7, 9 and 11), and one sample without pH adjustment was used as the control. Additionally, we synthesized AgNPs using the standard antioxidants gallic acid and rutin trihydrate. Our results showed that with increasing pH, changes in the color of solutions and escalation of UV–Vis spectrum absorbance were observed. The sizes and shapes of the AgNPs were further characterized using TEM and PSA, which revealed spherical and short rod-shaped particles. Our findings about the strength of the antioxidant activity of the Matoa stem bark aqueous extract under different pH conditions provide relevant information on the processes that can affect silver nanoparticle biosynthesis.